2020
DOI: 10.1002/jccs.202000051
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hierarchical LiNixCoyMnzO2 from solvothermal [NixCoyMnz](OH)2 via regulating the ratio of Ni, Co, and Mn and its excellent properties for lithium‐ion battery cathode

Abstract: The ternary-layered oxide (LiNi x Co y Mn z O 2) has become the most promising cathode material for lithium-ion batteries due to the advantages of higher discharge platform, better conductivity, and higher theoretical capacity. The [Ni x Co y Mn z ](OH) 2 with different ratios of nickel, cobalt, and manganese (NCM) was prepared by solvothermal method, and then ternary cathode material LiNi x Co y Mn z O 2 was obtained by mixing lithium and calcining. In this paper, ternary cathode materials with different rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…These complexes are unexpected products and the structures are unusual. On the basis of our previous research results, we believe that the reaction pathway may undergo a process of carbon radical generation and coupling. A proposed mechanism for the formation of these complexes is proposed in Scheme .…”
Section: Resultsmentioning
confidence: 79%
“…These complexes are unexpected products and the structures are unusual. On the basis of our previous research results, we believe that the reaction pathway may undergo a process of carbon radical generation and coupling. A proposed mechanism for the formation of these complexes is proposed in Scheme .…”
Section: Resultsmentioning
confidence: 79%
“…Similar observations were made in other conversion reaction compounds and might originate from the (i) sluggish kinetics of Na ion transfer in conversion reaction because of their larger ion size and (ii) different nature of the SEI layer formed in Na cells. [386][387][388][389][390][391][392][393] Recently, Zhang et al reported a 3D porous Fe 2 O 3 /C nanocomposite as a high-performance anode for NIBs. [ 394 ] The nanocomposite was composed of interconnected nanochannels and Fe 2 O 3 nanoparticles that were uniformly incorporated in a conductive porous carbon matrix.…”
Section: Conversion Reaction Compoundsmentioning
confidence: 99%
“…Emodin is a dihydroxyl-like derivative ( Figure 2), and has various pharmacological activities such as anti-inflammatory, antibacterial, antiviral, antioxidant, liver-protecting, anti-tumor, and so on. [15,16] However, emodin is hardly soluble in water and is not easy to absorb in the body, and its bioavailability is low. Huang et al obtained the best formula of emodin self-microemulsion [17] through solubility study, compatibility test, pseudoternary phase diagram analysis and central composite design.…”
Section: Anthraquinonesmentioning
confidence: 99%